Analisis Sentimen Mahasiswa terhadap Kuesioner Penilaian Pelayanan Sekretariat FTKI Universitas Nasional dengan menggunakan Metode Simple Multi Attribute Rating Technique (SMART) dan Simple Additive Weighting (SAW) - Arika Zuraidah; Agung Triayudi; Andrianingsih Andrianingsih (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
In the world of higher education, service to students is very much needed, it is very important to maintain the quality of service so that good and disciplined service to students can be realized. This sentiment analysis aims to determine student opinion made using a questionnaire form. In addition, the Decision Support System with the Simple Multi Attribute Rating Technique (SMART) and Simple Additive Weighting (SAW) methods is expected to be a solution in providing an assessment of the FTKI secretariat services. This study uses a questionnaire form to see student assessments and make it an alternative value. The final results are obtained by testing the order analysis technique, which is 82%, proving that by testing these two methods, service assessment can be more expanded.